Enrichment dynamics of Listeria monocytogenes and the associated microbiome from naturally contaminated ice cream linked to a listeriosis outbreak. Issue 1 (December 2016) - Ottesen, Andrea; Ramachandran, Padmini; Reed, Elizabeth; White, James; Hasan, Nur; Subramanian, Poorani; Ryan, Gina; Jarvis, Karen; Grim, Christopher; Daquiqan, Ninalynn; Hanes, Darcy; Allard, Marc; et al.
Abstract Background Microbiota that co-enrich during efforts to recover pathogens from foodborne outbreaks interfere with efficient detection and recovery. Here, dynamics of co-enriching microbiota during recovery ofListeria monocytogenes from naturally contaminated ice cream samples linked to an outbreak are described for three different initial enrichment formulations used by the Food and Drug Administration (FDA), the International Organization of Standardization (ISO), and the United States Department of Agriculture (USDA). Enrichment cultures were analyzed using DNA extraction and sequencing from samples taken every 4 h throughout 48 h of enrichment. Resphera Insight and CosmosID analysis tools were employed for high-resolution profiling of 16S rRNA amplicons and whole genome shotgun data, respectively. Results During enrichment, other bacterial taxa were identified, includingAnoxybacillus, Geobacillus, Serratia, Pseudomonas, Erwinia, andStreptococcus spp. Surprisingly, incidence ofL. monocytogenes was proportionally greater at hour 0 than when tested 4, 8, and 12 h later with all three enrichment schemes. The corresponding increase inAnoxybacillus andGeobacillus spp. indicated these taxa co-enriched in competition withL. monocytogenes during early enrichment hours.L. monocytogenes became dominant after 24 h in all three enrichments. DNA sequences obtained from shotgun metagenomic data ofListeria monocytogenes at 48 h were assembled to produce a consensus draft genome which appeared to have a similar tracking utility to pure culture isolates ofL. monocytogenes . Conclusions All three methods performed equally well for enrichment ofListeria monocytogenes . The observation of potential competitive exclusion ofL. mono byAnoxybacillus andGeobacillus in early enrichment hours provided novel information that may be used to further optimize enrichment formulations. Application of Resphera Insight for high-resolution analysis of 16S amplicon sequences accurately identifiedL. monocytogenes . Both shotgun and 16S rRNA data supported the presence of three slightly variable genomes ofL. monocytogenes . Moreover, the draft assembly of a consensus genome ofL. monocytogenes from shotgun metagenomic data demonstrated the potential utility of this approach to expedite trace-back of outbreak-associated strains, although further validation will be needed to confirm this utility.